Vue JS 2 : the complete guide (incl. Vue Router and Vuex) (Packt Publishing, 2018)
"Whichever metric you look at (Google Trends, Github Stars, Tweets ...) VueJS is the shooting star in the world of JavaScript frameworks - it simply is amazing! Frontend frameworks are extremely popular because they give us this reactive, great user experience we know from mobile apps, but now in the browser! No wonder that jobs requiring frontend framework skills like VueJS are amongst the best-paid ones in the industry! You may know Angular 2 and ReactJS, well, VueJS combines the best of both frameworks and makes building anything from small widgets to big, enterprise-level apps a breeze and a whole lot of fun! And if you don't know the two mentioned frameworks: That's fine, too, this course does not expect any knowledge of any other frontend framework - you will learn it all throughout this course! This course covers it all! We'll start at the very basics, what Vue.js is and how it works before we move on to more complex and advanced topics. And all this is accompanied with many exercises and multiple course projects - because it isn't just about seeing code, it's about using and practicing it!"--Resource description page